Analisis Dan Perancangan Sistem Penunjang Keputusan Pemilihan Program Studi Pada Universitas Adiwangsa Jambi - Iswanti, Dewi Nur; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2020)
Adiwangsa Jambi University, is a change in form and an increase in status of Stikes Prima Jambi. Adiwangsa Jambi University (UNAJA) located on St. Sergeant Muslim RT. 24 Coffee Plantation Exit Thehok South Jambi Jambi City. Has 5 faculties including the Faculty of Health & Pharmacy, Faculty of Engineering & Computer Science, Teacher Training & Education Faculty, Faculty of Economics, and Faculty of Law. some new students who register are still confused with the choice of concentration of study programs at Adiwangsa University Jambi. Errors in the selection of this study program will have an unfavorable impact when the student follows a course that is taught, among others, understanding the material and there are also less capable of the subjects he took. To overcome these problems researchers conduct research with the aim of designing a prototype system to support the selection of study programs that will later solve existing problems.